Salivary Cortisol Levels Representing Serum Cortisol Levels in Atopic Dermatitis Patients - Adisty, Novia Indriyani; Hutomo, Marsudi; Indramaya, Diah Mira (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Atopic dermatitis (AD) is a chronic inflammatory skin disorder, recurrent lesion with a distinctive and specific distribution of lesions according phases. Patients with allergic diseases have been known to have a variety of patterns of cortisol. Dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis and the role of cortisol has been studied in patients with DA. Free cortisol adrenal cortex is considered biologically active, which passively diffuses into all body fluids including saliva. Another advantage is the saliva examination is non-invasive, stress free and easy to do anywhere. Purpose: To analyze the correlation between levels of serum cortisol and salivary cortisol in patients with AD. Methods: Analytical, observational, cross-sectional study of the 29 AD patients who underwent blood and saliva samples by the method of "passive drooling" conducted on the hour 8:00 to 9:00 to see the levels of serum cortisol and salivary cortisol. Results: Twenty-nine subjects revealed mean serum cortisol levels 6,703,82g/dL, mean salivary cortisol levels was 1,430,96g/dL. Equation of salivary cortisol = 0,471+0,142*serum cortisol 2 (R=28,5%). Conclusions: The increasing of serum cortisol level of AD patients will result in increased levels of cortisol in saliva. Saliva collection methods by âpassive droolingâ were able to describe the serum cortisol levels at 28,5%.Key words: atopic dermatitis, serum cortisol, salivary cortisol.